2017
DOI: 10.1590/s1677-5538.ibju.2015.0117
|View full text |Cite
|
Sign up to set email alerts
|

Cystometric analysis of the transplanted bladder

Abstract: Objective Cystometric evaluation of the bladder after autotransplant and isogeneic transplant in female rats.Material and Methods Two groups were constituted: (A) bladder autotransplant with two subgroups: R1 – (control) and R2 – (bladder transplant); (B) isogeneic bladder transplant with three subgroups; T1 – (control); T2–T3, two subgroups observed for 30 and 60 days after transplant, respectively. All animals underwent cystometric evaluation. Afterwards, the bladders were removed for histological study.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…However, these tests employed in metabolic cages cannot determine whether the Trp mice were able to completely empty their bladder (bladder voiding efficiency). To further evaluate test the bladder function and voiding efficiency, we subjected Ctrl and Trp mice to cystometry 13,14 . Briefly, a catheter was inserted into the bladder under microscopic guidance (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these tests employed in metabolic cages cannot determine whether the Trp mice were able to completely empty their bladder (bladder voiding efficiency). To further evaluate test the bladder function and voiding efficiency, we subjected Ctrl and Trp mice to cystometry 13,14 . Briefly, a catheter was inserted into the bladder under microscopic guidance (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate test the bladder function and voiding efficiency, we subjected Ctrl and Trp mice to cystometry. 13,14 Briefly, a catheter was inserted into the bladder under microscopic guidance ( Figure 2D). Two weeks after catheter insertion, the mice were placed on the cystometry machine, saline was steadily infused into the bladder through inserted catheter, and voiding pressure and volume were automatically monitored for more than 2 hours.…”
Section: To Test the Urine Secretion Ability Under Natural Conditionsmentioning
confidence: 99%
“…The form, vascularity and survival remain hypothetical but there is no promise of function as the graft has no neural connection proposed. In a rat model supra trigonal cystectomy and isogenic transplant did show functional recovery; 4 however, the rat has the ability to regenerate bladder and function. 5 Extrapolation in humans is to be determined.…”
mentioning
confidence: 93%
“…There has been one reported case of transplanting a human urinary bladder en bloc with pediatric kidney transplantation, but that was back in 2008 3 . A 2017 Brazilian study reported feasibility of bladder transplants in rats 4 . While the path from proof of concept in a mouse model to clinical use in human patients is obviously long and uncertain, the mouse model presented in this edition of the AJT provides a good starting place.…”
mentioning
confidence: 99%